THE COOPERATION OF GOVERNMENT AND PRIVATE ORGANIZATION IN FARMERS POVERTY REDUCTION - Saifuddin Yunus; Suadi Zainal; Fadli Jalil (AIBPM Publisher, 2019)
This research aims to explain the cooperation between government and the private sector in poverty reduction of oil palm farmers in East Aceh, Indonesia. The research used a qualitative method; the data were collected by dept interview and documents study, and then analyzed with the interactive model. The results reveal that the cooperation of the government department and the private organization has been done automatically due to normative procedural demands, but there are no synergy efforts focused on oil palm plantation and cattle integration. However, the integrated model not only provides economic benefits but provides social benefits for farmers.